Bilayer Fiber‐Reinforced Composite‐Hydrogel Scaffolds With Bioactive Glass for Bone Tissue Regeneration - Gibreel, Mona; Ohlsbom, Roope; Perea‐Lowery, Leila; Lassila, Lippo; Puistola, Paula; Hopia, Karoliina; Miettinen, Susanna; Mörö, Anni; Vallittu, Pekka K. (Wiley, 2026)
Bone tissue regeneration for large defects presents a significant challenge, demanding scaffolds that combine robust mechanical support alongside a bioactive environment. Hydrogels represent a promising solution for bone regeneration due to their biocompatibility, tunable properties, and crosslinked three-dimensional (3D) networks mimicking the natural extracellular matrix (ECM). However, their mechanical properties remain suboptimal for restoring bone defects effectively. This study introduces a novel bilayer laminate scaffold, integrating a biostable fiber-reinforced composite (FRC) with a biodegradable, 3D-printed hyaluronic acid (HA)-based hydrogel. To enhance bioactivity, bioactive glass (BAG) was incorporated into the hydrogel layer. Comprehensive characterization confirmed the scaffold's chemical and morphological properties, as well as its controlled degradation, sustained ion release, and bioactivity. Additionally, the study revealed that the BAG-induced alkaline pH shift (up to 9.24) affected hydrazone crosslinking efficiency, resulting in reduced hydrogel stiffness (86 ± 8 Pa versus 150 ± 4 Pa in control). The system showed excellent cytocompatibility, supporting high viability and proliferation of human bone marrow stem cells (BMSCs) embedded within the hydrogel component. The developed scaffolds promoted osteogenic differentiation, as evidenced by increased ALP activity and upregulated expression of osteogenic marker genes. Nevertheless, BAG incorporation did not enhance early osteogenic differentiation compared to control scaffolds. In conclusion, this bilayer scaffold offers a promising platform for bone tissue engineering (TE), providing some insights into the chemical interplay between inorganic fillers and hydrogel matrix for optimizing future scaffold designs.